PENGEMBANGAN E-MODUL PJBL QR CODE UNTUK MENINGKATKAN BERFIKIR KREATIF PESERTA DIDIK: berfikir kreatif, pengembangan e-modul, pjbl - Puspita Ningrum, Wahindun Dewi Ayu; Achyani; Widowati, Hening (Universitas Muhammadiyah Metro, 2025)
To foster student creativity through providing knowledge and instructional resources in the form of independent online courses. E-modules are learning resources that are logically organized so that students can access them at any time and from any location. The aim of developing this product is to provide goods in the form of e-modules that are useful and make it easier for students to study biology independently. To ensure the feasibility and success of the product to be tested, research and development (R&D) is the research methodology used, using a 4D model consisting of defining, designing, developing and disseminating. Based on the results of the development of the Pjbl e-module assisted by Qr Code, it was concluded that the e-module is good and suitable for students to use, it can increase student independence and help students achieve learning goals.